2018
DOI: 10.5604/01.3001.0012.0486
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging in transoral laser microsurgery (TLM) in moderately advanced (T2, T3) glottic cancer

Abstract: Introduction: Treatment planning in T2, T3 laryngeal carcinoma is based on clinical assessment and radiological imaging. However, to delineate precise mucosal margins for transoral laser microsurgery (TLM), a high class, sophisticated endoscopy is indispensable. Narrowband imaging (NBI) which is an optical filter technology, seems to be a useful adjunctive tool in marking superficial margins. Materials and Methods: A total of 98 patients diagnosed with HNSCC underwent cordectomies and were enrolled in the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Piersiala et al in a sample of 98 patients reported that the intraoperative use of WL and NBI provided negative margins in all patients; however the use of NBI allowed identification of lesions invisible in WL in 10 patients (10.2%) that required further samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Piersiala et al in a sample of 98 patients reported that the intraoperative use of WL and NBI provided negative margins in all patients; however the use of NBI allowed identification of lesions invisible in WL in 10 patients (10.2%) that required further samples.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, five primary research papers met the minimum eligibility criteria and were included in the systematic review. They included three retrospective studies , one descriptive study , and one prospective study . The main characteristics of the selected studies (type of study, length of follow‐up, and principal endpoint investigated) are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Definitions of surgical margins status in laryngeal cancer depend on the T stage of the primary tumour. Some experts distinguish ultra negative margins defined as >1 mm in T1 glottic cancer [10,11] and >3 mm in T2-T3 glottic cancer [10]. In our paper, we decided to unify margins definition criteria for the whole group.…”
Section: Discussionmentioning
confidence: 99%